SAT0224 ANTIPHOSPHOLIPID ANTIBODIES AND VASCULAR RENAL LESIONS AS PROGNOSTIC FACTORS IN LUPUS NEPHRITIS. (2nd June 2020) - Paglionico, A.; Varriano, V.; Petricca, L.; Vischini, G.; DI Mario, C.; Gigante, M. R.; Tanti, G.; Costanzi, S.; Grandaliano, G.; Tolusso, B.; Ferraccioli, G.; Gremese, E.
Abstract : Background: Several studies have showed that antiphospholipid antibodies (aPL) positivity represents a predictor of worse renal outcome in patients with Lupus Nephritis (LN). In addition, an association between aPL positivity and the histological data of vascular lesions on the renal biopsies has been reported. Objectives: To determine the prognostic role of aPL and vascular renal lesions in the assessment of clinical outcome during the follow up period, in terms of time to achieve remission, number of renal flares and development of chronic renal damage in patients affected by LN. Methods: Among 120 patients affected by LN from our Rheumatology Unit, 91 patients (age 43.8 ± 12 years, 74 (81.3%) female, disease duration 7.1 ± 7.9 years) have been evaluated and the follow-up data have been collected at the baseline and at 6, 12, 24 months and at the last follow-up visit. Histopathological data of 41 patients were evaluated according to the 2016 revision of ISN/RPS classification. Results: Among the 91 LN patients, 31 (34.1%) were aPL positive (aPL+), 10 (32.2%) of them were affected by Antiphospholipid Antibodies Syndrome (APS), 53.3% showed a single aPL positivity, 23.1% double aPL positivity and 15.4% triple aPL positivity. At the last follow up visit a significant higher number of aPL+ patients showed a persistent complement consumption than aPL negative (aPL-) patients (p=0.001). Evaluating clinical outcome, we observed that aPL- patients showed a remission achievement time slightly earlier than aPL+ patients (13.6 ± 1.0 months vs 16.5 ± 1.5 months; log-rank test: p=0.06, Breslow test: p=0.08) and as expected, patients with a persistent complement consumption achieve remission later (18.2 ± 1.5 months vs 13.0 ± 1 months; log-rank test: p=0.002, Breslow test: p=0.003). Furthermore at the last follow up, a significant higher percentage of aPL+ patients developed persistent proteinuria (p=0.02) and chronic renal failure (p=0.04). Considering histologic features (activity and chronicity index, glomerulonephritis class, presence of mesangiolysis, glomerular wrinkling, glomerular thrombi, interstitial inflammatory infiltrates, interstitial fibrosis and tubular atrophy, tubulitis and vascular lesions) we didn't observe significant differences between aPL+ and aPL- patients but we found two typical vascular lesions (mesangiolysis and vascular thrombi) only in aPL + patients. Conclusion: aPL positivity is a predictor of worse renal outcome but in our cohort of LN patients we didn't find an association between aPL positivity and vascular renal lesions at renal biopsy. The worse renal outcome and the late time to achieve remission in aPL+ group can be related to a cumulative vascular damage over time as observed in other organ and systems. Disclosure of Interests: None declared